DEVELOPING CONTEXTUAL TEACHING AND LEARNING-BASED LEARNING E-COMIC ON SOCIAL ARITHMETIC MATERIALS FOR JUNIOR HIGH SCHOOL GRADE VII - Dianing Meijayanti; bambang Sumarno (Jurnal Pedagogi Matematika, 2016)
AbstractThis research was aimed  to develop e-comic learning based on Contextual Teaching and Learning (CTL) on mathematics learning arithmetic socials materials for junior high school grade VII, and to evaluate the products quality in terms of their validity, practicality, and effectiveness. This was a developmental  research  based  on  ADDIE  model  consisting  of  analysis,  design,  development, implementation, and evaluation. The developed were tried out to 32 students of grade VII-8 at SMP N  8 Yogyakarta.  The  instrument  that  used  to  evaluate  the  e-comic  qualities  consisted  of  e-comic assessment  sheet  for  material  and  media  experts,  lesson  plan  assessment  sheet,  response questionnaire  (for  students  and  teacher),  and  student  achievement  test.  The  quality  of  e-comic learning in terms of validity was very good, according to the collected data that the e-comic obtained average score 8,23 and lesson plan obtained average score 8,32. In terms of practicality, they were good, according to the student response to the questionnaire obtained average score  4,00 and the teacher response to the questionnaire obtained average score 4,09. In terms of effectiveness, they were very good, according to the student achievement test, which was at percentage level 87,50%. Keywords: e-comic learning, CTL, arithmetic socials